ENVIRONMENTAL IMPACT ASSESSMENT OF NUCLEAR DESALINATION PLANT AT KANUPP - Saleem, M. (The Nucleus, 2010)
A Nuclear Desalination Demonstration Plant (NDDP) of 1600 m3 /d capacity is being installed at Karachi Nuclear Power Plant (KANUPP). A Nuclear Desalination Plant (NDP) can impact the aquatic environment mainly by subjecting the aquatic life to possible temperature increase and salinity changes in the vicinity of the cooling water and brine discharges. Any wastewater effluent, which will be discharged from the NDDP, may have some adverse effects on the marine life and general environment. In order to protect the environment and comply with the requirement of the Pakistan Environmental Protection Agency (PEPA) an Environmental Impact Assessment (EIA) for the discharged effluent from NDDP was carried out. In the present work baseline study was carried out for project location, climate, water resources, and ecology. Checklist has been prepared for identification of possible environmental impacts of the project and marked as insignificant, small, moderate or major impact. Appropriate mitigation measures have been recommended that can be incorporated into the intended program to minimize environmental impacts identified during the assessment. Specific conclusions of the study and recommendations have also been provided in this paper.